2D seismic response of shallow sandy basins subjected to obliquely incident waves - Khanbabazadeh, Hadi; Iyisan, R.; Ozaslan, B. (Elsevier Sci Ltd, 2022)
Under the effects of the near-field earthquakes, the change in the incident angle of the incoming wave changes the symmetric response of basins to asymmetric. This paper investigates the 2D response of shallow trapezoidal sandy basins to incident plane SV waves. To attain this goal, a trapezoidal basin with 100 m depth, as the representative of shallow sedimentary basins, with an inclined bedrock angle of 10 degrees was selected. These values fall inside of the ranges of the shallow basin depth and bedrock angle of several real basins. To make the results useful in engineering affairs, three different sand types belonging to the different class of soils, with respect to the soil classification codes, were selected. The constructed models were subjected to the collection of 24 earthquakes with different PGA's of 0.1, 0.2, 0.3 and 0.4 g using a fully nonlinear method. The results showed that the change in the incident angle of the motions not only affects the response at two basin edges but also influences the response of the central part. Among different sandy basins, the behavior of the basin with medium dense sand is less affected by the change in the wave incident angle. For basin with loose sand, while greater maximum spectral amplifications happen at the backward direction of the basin, the forward direction is less affected by the change in the wave incident angle. A different pattern was seen for basin with dense sand. Greater maximum spectral amplifications were seen at the forward direction of the basin. Regarding the effect of motion incident angle on the amplification frequency of shallow basins, it was seen that in case of the obliquely incident waves the spectral amplification curves of the points close to the edges have more than one (generally two) maximum points. Besides, unlike the vertical incident wave case that the SAF curves tend to almost one curve at the distant points from edges, no convergence among the SAF curves of the surface points was seen for the obliquely incident wave condition.
Keywords: Basin edge effect; Site effects; Incident angle; Dynamic behavior; Numerical modeling; Nonlinear analysis; Amplification factor; Aggravation factor